Court review of cases related to the determination of the origin of children: on unresolved procedural problems - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2020)
The article analyses some of the problems that courts face when considering cases of establishing the origin of children. In particular, the author considers issues such as whether it is permissible to accept a statement of claim for proceedings if the defendant’s place of residence is unknown, on whose initiative the limitation period is applicable, what are the conditions for a court to accept a plaintiff’s refusal of a claim and recognition of the claim by the defendant, whether the process can lose its subject. On this basis, the othour of the article makes suggestions for improving the legislation and practice of its application.
Keywords: establishment of paternity; contesting paternity; civil proceedings; place of residence of the defendant; the plaintiff's refusal of the claim; recognition of the claim by the defendant; change in the basis of the claim; subject of the process